Unlocking young women’s potential? The impact of a low-cost career guidance program - Asri, Ankush; Asri, Viola; Hoeffler, Anke (Journal of development economics, 2026)
Societal expectations and gender norms constrain young people’s career planning, particularly for girls, limiting the role of personal interests in skill-building decisions. This study evaluates a low-cost, 10-hour career exploration intervention through a pre-registered, school-level, clustered randomized controlled trial with over 6,000 primarily female students in urban India. The program improved future planning and increased the importance students placed on personal interests in career choices. However, there is no evidence of medium-term impacts on educational or skill-building investments. These findings suggest that while scalable interventions can shift aspirations and planning, structural barriers constrain longer-term behavioral change.